Improving the energy density of Li-ion capacitors using polymer-derived porous carbons as cathode - Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Electrochimica Acta, 2014)
High energy density Li-ion hybrid electrochemical capacitors (Li-HEC) are fabricated with 3 D architectured high surface area porous carbon (HSPC) derived from the poly(acrylamide-co-acrylic acid) potassium salt in a single step without any activating agent. The obtained HSPC exhibits high specific surface area of 1490 m(2) g(-1) and characterized with several analytical techniques. Li-HEC is fabricated with insertion type Li4Ti5O12 anode by adjusting the mass balance based on the single electrode performance with Li. The Li-HEC delivered the maximum energy density of similar to 55 Wh kg(-1), which is much higher than commercially available activated carbon (similar to 36 Wh kg(-1)). Further HSPC based Li-HEC delivered excellent cycleability and rendered similar to 87% of initial value after 2000 cycles. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: energy density; Li-ion hybrid electrochemical capacitors; non-aqueous; porous carbon

Graphene oxide sheathed ZIF-8 microcrystals: engineered precursors of nitrogen-doped porous carbon for efficient oxygen reduction reaction (ORR) electrocatalysis - Thomas, Minju; Illathvalappi, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, Abdul Azeez Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (ACS Applied Materials & Interfaces, 2016)
Nitrogen containing mesoporous carbon obtained by the pyrolysis of graphene oxide (GO) wrapped ZIF-8 (Zeolitic Imidazolate Frameworks-8) micro crystals is demonstrated to be an efficient catalyst for the oxygen reduction reaction (ORR). ZIF-8 synthesis in the presence of GO sheets helped to realize layers of graphene oxide over ZIF-8 microcrystals and the sphere-like structures thus obtained, on heat treatment, transformed to highly porous carbon with a nitrogen content of about 6.12% and surface area of 502 m(2)/g. These catalysts with a typical micromeso porous architecture exhibited an onset potential of 0.88Vvs RHE in a four electron pathway and also demonstrated superior durability in alkaline medium compared to that of the commercial Pt/C catalyst. The N-doped porous carbon derived from GO sheathed ZIF-8 core shell structures could therefore be employed as an efficient electrocatalyst for fuel cell applications.
Keywords: alkaline fuel cell; graphene oxide; N-doped carbon; oxygen reduction reaction; porous carbon; ZIF-8